Manajemen Kesiswaan untuk Peningkatan Employability Skills Siswa SMK: Kajian Sistematis Terhadap Program Pembinaan dan Magang - Pebrianti, Laras; Jalinus, Nizwardi; Ernawati, Ernawati; Yustisia, Henny (Reflection Journal, 2025)
Peningkatan employability skills siswa Sekolah Menengah Kejuruan (SMK) merupakan fokus utama reformasi pendidikan vokasi, menuntut keterpaduan erat antara sekolah dan dunia industri. Penelitian ini bertujuan untuk menganalisis bagaimana bagaimana manajemen kesiswaan dapat menjadi pilar utama dalam meningkatkan employability skills siswa SMK melalui program pembinaan dan magang. Metode yang digunakan adalah Systematic Literature Review (SLR) dengan pendekatan PRISMA yang menelaah 12 artikel ilmiah terbitan tahun 2022-2025 dari berbagai basis data akademik. Hasil kajian menunjukkan bahwa manajemen kesiswaan tidak lagi bersifat administratif, melainkan instrumen strategis yang membangun karakter kerja, kedisiplinan, dan etos kerja berkelanjutan. Pendekatan manajemen kesiswaan yang adaptif, berbasis data, dan kolaboratif, terutama yang mengintegrasikan pembinaan karakter, pengembangan kreativitas, dan digitalisasi proses magang, terbukti meningkatkan kesiapan kerja siswa hingga 35%. Kebaruan penelitian ini terletak pada perumusan kerangka konseptual integratif yang menghubungkan manajemen kesiswaan, pembinaan, dan magang sebagai satu kesatuan sistem penguatan employability skills. Temuan ini memiliki implikasi penting bagi pengembangan kebijakan pendidikan vokasi dan praktik manajemen SMK yang berorientasi pada kebutuhan pasar kerja global. Student Management for Enhancing the Employability Skills of Vocational School Students: A Systematic Review of Mentoring and Internship Programs Improving the employability skills of vocational high school (SMK) students is the main focus of vocational education reform, requiring close integration between schools and industry. This study aims to discuss how student management can be a key pillar in improving the employability skills of SMK students through structured and sustainable coaching and internship programs. Using a Systematic Literature Review (SLR) methodology guided by the PRISMA framework, this study analyzes various relevant academic and vocational policy literature. The findings show that student management is no longer administrative in nature, but rather a strategic instrument that builds work character, discipline, and a sustainable work ethic. An adaptive, data-driven, and collaborative approach to student management, especially one that integrates character building, creativity development, and digitization of the internship process, has been proven to increase student work readiness by up to 35%. Specific aspects of student guidance improve crucial soft skills such as creativity, communication, and teamwork. Furthermore, internship or PKL programs provide real work experience, but their effectiveness is highly dependent on strong partnership management between schools and industry. Thus, the integration of student management, coaching, and internships, in line with link and match policies, is an essential systematic strategy for achieving employability outcomes relevant to the demands of the global job market.